Estudio molecular de alteraciones del eje Hipotálamo-hipófiso- IGF-1 en población pediátrica Argentina con déficit de crecimiento - Juanes, Matías Hernán (2016)
Normal somatic growth requires the integrated function of many of the hormonal, metabolic, and other growth factors involved in the hypothalamo-pituitary-IGF-1 growth axis.\nSeveral genetic variations in genes involved in the hypothalamo-pituitary-IGF-1 growth axis have been described as the cause of short stature, however, the real prevalence has not been determined. The phenotype of growth hormone deficiency includes many different pathologies which we classified into four groups: 1) Isolated growth hormone deficiency, as a consequence of mutations in GH1 and GHRHR genes; 2) GH-1 insensibility syndrome, due to mutations in GHR and STAT5b gene; 3) IGF-1 resistance, due to mutations in IGF1R gene; 4) Multiple pituitary hormone deficiency as a consequence of alterations in genes which play a role in the regulation of pituitary differentiation and early development (PROP1, POU1F1, LHX3, LHX4, HESX1, OTX2, GLI2).\nThe molecular characterization of the genes implicated in the hypothalamo-pituitary-IGF-1 growth axis is important for the diagnosis as it directly impacts in the therapeutic strategy and genetic counseling. The main objective of the present doctoral thesis is the molecular characterization of pediatric patients with alterations in the mentioned axis.